It’s just becoming such a burden on us in the community - Chan Soo, Rhonda (Instituto Interamericano de Ciencias Agrícolas (IICA), 2023)
Benjamin shares his experiences, which many residents in several rural communities across the Caribbean can relate to, living with the real, not projected impacts of climate change. Climate change impacts are threatening vulnerable areas with a ‘back to nature’ outcome, but definitely a very different and more inhospitable nature for humans and community lives and livelihoods.